Cumulative Innovation and Competition Policy - Alexander Raskovich; Nathan H. Miller (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2010)
We model a "new economy" industry where innovation is sequential and monopoly is persistent but the incumbent turns over periodically. In this setting we analyze the effects of "extraction" (e.g., price discrimination that captures greater surplus) and "extension" (conduct that simply delays entry of the next incumbent) on steady-state equilibrium innovation, welfare and growth. We find that extraction invariably increases innovation and welfare growth rates, but extension causes harm under plausible conditions. This provides a rationale for the divergent treatment of single-firm conduct under U.S. law. Our analysis also suggests a rule-of-thumb, consistent with antitrust practice, that innovation proxies welfare.
Keywords: 330